The undergrowth composition and distribution in different forest area utilization (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sidabukke SH, Barus TA, Utomo B, Delvian. 2021. The undergrowth composition and distribution in different forest area utilization. Biodiversitas 22: 5255-5261. Forests provide natural raw materials to support various human activities and also demonstrate a wide range of biodiversity, both in terms of wildlife and plants. Based on biological resources, undergrowth species form a significant portion of the forest ecosystems and have overgrown the typical wooden plants. These ground cover/undergrowth groups are known to exhibit diverse complexities and a type of basic vegetation existing under the forest stands. Therefore, the purpose of this study is to determine the composition and distribution of undergrowth species in each forest area designation, including industrial, protected and natural forests. The plot technique was employed, with an area of 2 m x 2 m. This involves a total of 480, 224 and 96 plots in the industrial plantations, protected and natural forest areas, respectively. Also, the entire plants in the measuring plot were recorded, starting from the sprouts up to 1.5 m high. Subsequently, the important value index (IVI) and Morisita index methods were applied in the data analysis. The results showed the occurrence of 98, 57 and 33 undergrowth species in industrial, protected as well as in natural forests, correspondingly. Based on the important value index calculations, Sintrong species (Crassocephalum crepidioides) reported the maximum IVI (31.587%) in industrial forest plantations, alongside Senduduk (Melastoma malabathricum) and Paku Wangi (Phymatosorus scolependria) in the protected areas (29.951%) and natural forests (29.551%), respectively. Furthermore, the Morisita index indicated that the undergrowth distribution pattern for the three areas was clustered, uniform and random, but with varying percentages. However, only two distribution patterns, including random and clustered were peculiar to the natural forests.